Os fundos brasileiros de previdência complementar: Segmentaç\~oes analíticas e estudos preliminares sobre a alocaç\~ao de seus recursos - Bruno De Conti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Brazilian pension funds hold together a portfolio that exceeds R 1 trillion. This volume of resources justifies researches that try to understand the management of these portfolios. This paper aims therefore to analyze the allocation of the wealth managed by these funds. As an associated goal, the paper aims to evaluate the possibilities of this huge mass of resources to eventually constitute a funding for the long-term financing in Brazil. With these purposes, the paper suggests an analytical segmentation of the different kinds of pension funds, which shows that those with the greatest potential to provide this funding are the closed, large and public companies funds.
Keywords: G11; G23; 330; pension funds; financing; portfolio choice